2017
DOI: 10.3389/fpls.2017.01952
|View full text |Cite
|
Sign up to set email alerts
|

A Major Locus for Manganese Tolerance Maps on Chromosome A09 in a Doubled Haploid Population of Brassica napus L.

Abstract: Soil acidity poses a major threat to productivity of several crops; mainly due to the prevalence of toxic levels of Al3+ and Mn2+. Crop productivity could be harnessed on acid soils via the development of plant varieties tolerant to phytotoxic levels of these cations. In this study, we investigated the extent of natural variation for Mn2+ tolerance among ten parental lines of the Australian and International canola mapping populations. Response to Mn2+ toxicity was measured on the bases of cotyledon chlorosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…‘Darmor- bzh ’ is a French winter type and double-low oil quality cultivar, while ‘Yudal,’ is a Korean Spring type cultivar. Besides resistance to blackleg disease, this population also segregates for a range of traits such as plant height, flowering time, oil content ( Delourme et al, 2006b ) and quality, and tolerance to manganese (Mn 2+ ) toxicity ( Raman et al, 2017 ). ‘Darmor- bzh ’ carries the dwarf Bzh gene and is known to carry Rlm9 for qualitative resistance to L. maculans ( Foisset et al, 1995 ; Delourme et al, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…‘Darmor- bzh ’ is a French winter type and double-low oil quality cultivar, while ‘Yudal,’ is a Korean Spring type cultivar. Besides resistance to blackleg disease, this population also segregates for a range of traits such as plant height, flowering time, oil content ( Delourme et al, 2006b ) and quality, and tolerance to manganese (Mn 2+ ) toxicity ( Raman et al, 2017 ). ‘Darmor- bzh ’ carries the dwarf Bzh gene and is known to carry Rlm9 for qualitative resistance to L. maculans ( Foisset et al, 1995 ; Delourme et al, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…Total genomic DNA was isolated following a high throughout DNA protocol, essentially based on chloroform and phenol. A framework map of the DYDH population, based on 2,094 DArTseq markers was constructed as described previously ( Raman et al, 2014 , 2017 ). PCR based SCAR (sequence characterized amplified region) marker specific to Bzh gene for dwarfness was analyzed using the primer-pairs: SCM07UP1 and LP2 as described in Barret et al (1998) .…”
Section: Methodsmentioning
confidence: 99%
“…One of the highly significant association peaks was located close to the BnMn 2+ .A09 locus, previously identified by QTL analysis in the B. napus DH population (Raman et al, 2017). However, no QTL/eQTL for Mn 2+ tolerance on C03 and C09 chromosomes were identified in earlier studies.…”
Section: Bnmtp8a09 Controls Natural Variation For Mn 2+ Tolerance In ...mentioning
confidence: 79%
“…Natural variation for tolerance to Mn 2+ toxicity is described in several plant species, including Brassica napus (Foy, 1984, Horiguchi, 1988, Khan and McNeilly, 1998, Basu et al, 2001, Schaaf et al, 2002, Kassem et al, 2004, Peiter et al, 2007, Mizuno et al, 2008, Pradeep et al, 2020, Wratten and Scott, 1979, Moroni et al, 2003, Delhaize et al, 2003, Raman et al, 2017. Studies have shown that AtMTP11, BnMTP8.C04, BnMTP9.A07, ShMTP1, and NRAMP5 confer tolerance to Mn 2+ tolerance in plants (Gu et al, 2022, Delhaize et al, 2003, Delhaize et al, 2007, Noor et al, 2023.…”
Section: These Include Various Transporters Such As Natural Resistanc...mentioning
confidence: 99%
“…Only few studies have addressed genetic factors with Mn tolerance in plants (Wang et al, 2002;Kassem et al, 2004;Raman et al, 2017;Huang et al, 2018;Shrestha et al, 2018).…”
Section: Discussionmentioning
confidence: 99%